Effect of swim cap surface roughness on passive drag - Gatta, G.; Cortesi, M.; Zamparo, P. (The Journal of Strength and Conditioning Research, 2015)
In the last decade, great attention has been given to the improvements in swimming performance that can be obtained by wearing "technical swimsuits"; the technological evolution of these materials only marginally involved swim caps production, even if several studies have pointed out the important role of the head (as main impact point with the fluid) on hydrodynamics. The aim of this study was to compare the effects on passive drag (Dp) of 3 swim cap models: a smooth silicon helmet cap (usually used during swimming competitions), a silicon helmet cap with "dimples," and a silicon helmet cap with "wrinkles." Experiments were performed on 10 swimmers who were towed underwater (at a depth of 60 cm) at 3 speeds (1.5, 1.7, and 1.9 m/s) and in 2 body positions: LA (arms above the swimmer's head) and SA (arms alongside the body). The Dp values obtained in each trial were divided by the square of the corresponding speed to obtain the speed-specific drag (the k coefficient = Dp/v2). No differences in k were observed among swim caps in the LA position. No differences in k were observed between the smooth and dimpled helmets also in the SA position; however, the wrinkled swim cap helmet showed a significant larger k (4.4%) in comparison with the model with dimples, when the swimmers kept their arms alongside the body (in the SA position). These data suggest that wearing a wrinkled swim cap helmet can be detrimental to performance at least in this specific position.